Periorbital discoid lupus: a rare localization in a patient with systemic lupus erythematosus - Ozgur Cakici; Remzi Karadag; Huseyin Bayramlar; Seyma Ozkanli; Tugba Kevser Uzuncakmak; Ayse Serap Karadag (Sociedade Brasileira de Dermatologia, 2016)
Abstract A 40-year-old female patient with a 5-year history of systemic lupus erythematosus was referred to our policlinic with complaints of erythema, atrophy, and telangiectasia on the upper eyelids for 8 months. No associated mucocutaneous lesion was present. Biopsy taken by our ophthalmology department revealed discoid lupus erythematosus. Topical tacrolimus was augmented to the systemic therapeutic regimen of the patient, which consisted of continuous antimalarial treatment and intermittent corticosteroid drugs. We observed no remission in spite of the 6-month supervised therapy. Periorbital discoid lupus erythematosus is very unusual and should be considered in the differential diagnosis of erythematous lesions of the periorbital area..